Coastal conflict management planning a case study of selected barangays in Baler municipality, Aurora province, Philippines. - Cuevas, Jorge Vladimir Pasminio (2005)
The confluence of people and activities in the coastal sectors is a common phenomenon that occurs in many developing countries. Over the last decades, numerous authors and institutions have conducted studies on the coastal areas. This research analyzes a case study of the Municipality of Baler, in Aurora Province, where fishing has been the economic base of many people in this area. The study analyzed different issues such as environmental, political, and social conflicts that take place in coastal area of Baler. In this municipality, problems arise from the different human activities that take place in its coastal area which, in turn, adversely affects traditional fishing activities and the local environment. Coastal management has been traditionally a top-down approach which starts from the national administration and ends at the community level.This study shows that a bottom-up vision for coastal management, which begins with the local processes of coastal conflict management in Baler, can be the future approach for the other municipalities of Aurora Province. This is because it serves as a more important mechanism that can create a greater positive impact to the regional development of the coastal areas. The main objectives of this study is to the basic elements for a possible strategy for conflict management planning for fishers in the coastal areas of four (4) Barangays in Baler, namely, Pingit, Zabali, Reserva and Sabang. The study, however, limits the applicability of replication of the recommendations of the study to other coastal areas. Nevertheless, it does provide the basic process steps in conflict management and gives insight on coastal management for the fishing community. The thesis involved both primary and secondary data sources. Primary data collection was performed in June 2005 in Baler, using various data collection techniques such as Focus Group Discussion and Key Informant Interviews, and involved different stakeholders like members of fishermens' organizations, traders, government personnel. NGO representatives, and acdemicians. The secondary data included the documenetations ofdifferent international and national authors. Based on the analytical results of the study, the coastal conflicts which were pereceived and prioritized by the stakeholders in the coastal barangays of Baler...